2001
DOI: 10.1001/archpedi.155.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low Birth Weight on Early Childhood Asthma in the United States

Abstract: These data confirm findings of other studies that identify a strong independent association between low birth weight and asthma. For this 1988 national birth cohort, an estimated 4000 excess asthma cases were attributable to birth weight less than 2500 g. Although the strength of the independent association between VLBW and asthma was smaller in the African American population, the substantially increased prevalence of VLBW in this community may contribute to the disproportionately increased prevalence of asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 43 publications
4
81
1
2
Order By: Relevance
“…In the 1970 British Cohort Study, low birth weight was associated with asthma at 5 years but not after 16 years. Other studies have also reported a high prevalence of asthma among children born LBW 25 . The reason could be multifactorial such as prematurity, invasive lung ventilation during neonatal period and recurrent respiratory illness during early childhood 26,27,28 .…”
Section: Low Birth Weight and Asthmamentioning
confidence: 84%
“…In the 1970 British Cohort Study, low birth weight was associated with asthma at 5 years but not after 16 years. Other studies have also reported a high prevalence of asthma among children born LBW 25 . The reason could be multifactorial such as prematurity, invasive lung ventilation during neonatal period and recurrent respiratory illness during early childhood 26,27,28 .…”
Section: Low Birth Weight and Asthmamentioning
confidence: 84%
“…Results of 2 different analyses found that low birth weight accounted for 30% to 68% of the racial differences in asthma observed in the populations studied. 40,41 Residential segregation has the potential to shape socioeconomic conditions that can influence the risk of asthma development, including community-level and individual-level exposures. 42-44 Outdoor pollution has not been associated consistently with incident asthma, although it has been associated with increased symptoms among prevalent cases and is more often a problem in areas where people of less means reside.…”
Section: Race Ethnicity and Risk Factors For Asthmamentioning
confidence: 99%
“…LBW is defined as birth weight lower than 2,500 grams in singleton births (World Health Organization, 1992). Studies have linked LBW to childhood mortality (McCormick, 1985), morbidity (Wu et al, 2011), and childhood asthma (Brooks et al, 2001). LBW is also associated with disorders progressing into adulthood, such as metabolic syndrome (Fagerberg et al, 2004), type 2 diabetes (Johansson et al, 2008), cardiovascular diseases (Leeson et al, 2001), respiratory diseases (Walter et al, 2009), and depression (Thompson et al, 2001).…”
mentioning
confidence: 99%